Pengendalian Kualitas Kaoru Ishikawa pada Produk Sheet Karet di PT Perkebunan Nusantara XII Kotta Blater Jember - Indra Tjahaja Amir; Mubarokah Mubarokah (Fakultas Pertanian, Universitas Timor, 2022)
Indonesia as a rubber producer has a land area of ​​3,246.13 thousand hectares and production of 3.33 million tons in 2019. Compared to other rubber producing countries, Indonesia still has a low level of productivity. However, Indonesia is still not displaced from the second position in the world market. Indonesia's rubber productivity per year is only 1.08 tons/ha, while Thailand is 1.8 tons/ha and Malaysia 1,5 tons/ha. Rubber as an industrial material requires good quality assurance, so the plantation will try to carry out more intensive quality control in material, processes or final processes. The role of quality control is important to maintain good quality, so that the image of Indonesia will increase and compete in the world market. The research objectives are 1) to analyze the process of controlling products, 2) to analyze the number of defects in sheets that are still acceptable and 3) to analyze the total cost of optimal quality of products. The results showed that the quality control was based on international trade standards and the amount of damage to sheet rubber was 21.10%. Based on the control chart, product rejection caused by imperfect rubber processing resulted in non-standard color and bubbles. Total defective products through Kaoru Ishikawa's quality control is 6,485.50 kg per year, while the Statistical Quality Control has a small difference of 126.50 kg per year, or not significant.